OPTIMIZATION OF THE FOUR WHEEL PATROL UNITS OF SAMAPTA POLRES MAGELANG IN PREVENTION OF THE CRIME OF THE WEIGHTING BY WEIGHTING - Willem Rumbino (Indonesian Journal of Police Studies, 2022)
This research is motivated by the case of theft with a weight which is one of the highest criminal acts that occur in Magelang Regency. The Magelang Police took preventive action to prevent the crime of theft by weighting by optimizing the four-wheel patrol carried out by the Magelang Police Samapta Unit. The purpose of this research is to find out the process carried out by the Patrol Unit of the Samapta Unit in preventing the crime of theft by weighting and the efforts made in overcoming the factors that influence the inability of the Patrol. Theories and concepts used in this research are Swot Analysis and Management Theory, Drain Concept, Optimization Concept, Four Wheel Patrol Concept. This research uses a qualitative approach, with a descriptive analytical research type that seeks to systematically explain the facts about objects and their problems which are supported by the data obtained, as well as data collection techniques by interviewing, observing and reviewing documents. Based on the results of the study, the authors found the fact that there were several things that had not been fulfilled according to the regulations stipulated in Perkabaharkam No. 1 of 2017 concerning Patrol. There are several factors that influence the unfulfilled four-wheel optimization of the Magelang Police Samapta Unit, namely internal factors including Cooperation between Units, Personnel Experience, Lack of personnel and the presence of personnel mutations. Community and environmental external factors. Based on the research results, the authors provide input to the Magelang Police Samapta Unit to increase the number of personnel and carry out patrol management to the maximum.